Total joint replacement: A multiple risk factor analysis of physical activity level 1–2 years postoperatively. (15th June 2016) - Paxton, Elizabeth W; Torres, Andy; Love, Rebecca M; Barber, Thomas C; Sheth, Dhiren S; Inacio, Maria C S
Abstract : Background and purpose — The effect of total joint arthroplasty (TJA) on physical activity is not fully understood. We investigated the change in physical activity after TJA and patient factors associated with change. Patients and methods — Using a total joint replacement registry, primary total hip arthroplasty (THA) patients (n = 5, 678) and knee arthroplasty (TKA) patients (n = 11, 084) between January 1, 2010 and December 31, 2012 were identified. Median age at THA was 68 and median age at TKA was 67. Change in self-reported physical activity (minutes per week) from before TJA (within 1 year of surgery) to after TJA (1–2 years) was the outcome of interest. Patient demographics and comorbidities were evaluated as risk factors. Multiple linear regression was used. Results — Median physical activity before surgery was 50 min/week (IQR: 0–140) for THA patients and 58 (IQR: 3–143) for TKA patients. Median physical activity after surgery was 150 min/week (IQR: 60–280) for both THA patients and TKA patients. Following TJA, 50% of patients met CDC/WHO physical activity guideline criteria. Higher body mass index was associated with lower change in physical activity (THA: −7.1 min/week; TKA: −5.9 min/week). Females had lower change than males (THA: −11 min/week; TKA: −9.1 min/week). In TKA patients, renal failure was associated with lower change (−17 min/week), as were neurological disorders (−30 min/week). Interpretation — Self-reported minutes of physical activity increased from before to after TJA, but 50% of TJA patients did not meet recommended physical activity guideline criteria. Higher body mass index, female sex, and specific comorbidities were found to be associated with low change in physical activity. Patient education on the benefits of physical activity should concentrate on these subgroups of patients.